Considering intervention intensity in habitat restoration planning: An application to Pacific salmon. (1st December 2021) - Fonner, Robert; Honea, Jon; Jorgensen, Jeffrey C.; Plummer, Mark; McClure, Michelle
Abstract: Habitat restoration is a key strategy for recovering imperiled species, and planning habitat restoration activities cost effectively can help advance recovery objectives. Habitat restoration planning involves decisions about where and when to undertake restoration, and what type of restoration to undertake. This article focuses on decisions about the amount of restoration to undertake for a given type, location, and time, termed intervention intensity. A return on investment framework is developed for incorporating intervention intensity into habitat restoration planning. The framework is then applied in the context of planning habitat restoration for Pacific salmon recovery as a case study. Results showed that no single intervention type or location dominated, and several returns to scale relationships emerged across the candidate interventions. Scenarios that considered interventions across multiple intensities outperformed single-intensity scenarios in terms of total benefits and cost effectiveness. These findings highlight the usefulness of exploratory return on investment analysis for prioritizing habitat restoration interventions, and underscore the importance of systematically considering how much restoration to undertake, in addition to what to do and where. Highlights: Systematically considering the amount of restoration to undertake at a given location and time promotes effective habitat restoration planning. A return on investment framework is developed for considering intervention intensity when planning habitat restoration. The framework is applied to prioritizing habitat restoration for endangered Pacific salmon using coupled models of salmon habitat and salmon survival. The case study results illustrate that considering intervention intensity can promote cost-effective habitat restoration planning.